PENGARUH MANAJEMEN MODAL KERJA TERHADAP PROFITABILITAS PERUSAHAAN - Teguh Ardiansah; Ickhsanto Wahyudi (Akuntansi, 2022)
This research was conducted to partially analyze the Effect of Working Capital Management on Company Profitability in automotive sub-sector companies listed on the Indonesia Stock Exchange (IDX). The sampling method is purposive sampling. The number of samples used in this study were 10 automotive sub-sector companies listed on the Indonesia Stock Exchange (IDX) with a total sample of 50 data. This type of data is secondary data sourced from financial report data and annual reports. The data analysis method used is multiple linear regression analysis. The findings of this study are based on the results of the t test, it can be concluded that partially Days Sales of Inventory (DSI) partially has a positive and significant effect on company profitability in the automotive subsector listed on the Indonesia Stock Exchange (IDX) for the 2015-2019 period. Partially Days Sales Outstanding (DSO) and Days Payable Outstanding (DPO) have a negative and significant effect on company profitability in the automotive subsector listed on the Indonesia Stock Exchange (IDX) for the 2015-2019 period.